Servius and Virgil: Lessons in gender agreement - Vaahtera Jaana (United States, 2022)
In the article, I propose that the commentary on Virgil by the grammarian Servius shows
us how gender agreement was approached in school texts or school contexts. In focusing on the
actual process of Latin composition, his approach differs from the usual one found in
ancient Roman grammatical writings.